PERSONAL HYGIENE BEHAVIOR OF FEMALE PRISONERS' GENITALIA IN EFFORTS TO FULFILL REPRODUCTIVE HEALTH RIGHTS AT CLASS IIB PACITAN STATE DETENTION CENTER - Wattimena, Dewi; Soge, Markus Marselinus (Universitas Nusa Cendana, 2025)
This study aims to examine the personal hygiene behavior of female inmates' genitalia at Class IIB Pacitan Prison and identify the factors influencing it. Using a descriptive qualitative approach, this study found that although prisoners generally exhibit good hygiene behavior, there are still some obstacles that need to be addressed. Limited facilities, lack of female medical personnel, and minimal socialization regarding reproductive health are the main hindering factors. These findings indicate the importance of comprehensive efforts to improve the quality of reproductive health services in correctional facilities to meet the basic rights of female inmates. Keywords: Personal Hygiene; Female Prisoners; Reproductive Health Rights; Detention Center